Elevations in End-Tidal CO2 With CO2 Use During Pediatric Endoscopy With Airway Protection: Is This Physiologically Significant?. Issue 5 (22nd February 2023) - Dike, Chinenye R.; Huang Pacheco, Andrew; Lyden, Elizabeth; Freestone, David; Choudhry, Ojasvini; Bishop, Warren P.; Shukry, Mohanad
Abstract : Background: Inflation of the gastrointestinal lumen is vital for proper visualization during endoscopy. Air, insufflated via the endoscope, is gradually being replaced with carbon dioxide (CO2 ) in many centers, with the intention of minimizing post-procedural discomfort due to retained gas. Recent studies suggest that the use of CO2 during pediatric esophagogastroduodenoscopy (EGD) with an unprotected airway is associated with transient elevations in exhaled CO2 (end-tidal CO2, EtCO2 ), raising safety concerns. One possible explanation for these events is eructation of insufflation gas from the stomach. Objectives: To distinguish eructated versus absorbed CO2 by sampling EtCO2 from a protected airway with either laryngeal mask airway (LMA) or endotracheal tube (ETT), and to observe for changes in minute ventilation (MV) to exclude hypoventilation events. Methods: Double-blinded, randomized clinical trial of CO2 versus air insufflation for EGD with airway protection by either LMA or ETT. Tidal volume, respiratory rate, MV, and EtCO2 were automatically recorded every minute. Cohort demographics were described with descriptive characteristics. Variables including the percent of children with peak, transient EtCO2 ≥ 60 mmHg were compared between groups. Results: One hundred ninety-five patients were enrolled for 200 procedures. Transient elevations in EtCO2 of ≥60 mmHg were more common in the CO2 group, compared to the air group (16% vs 5%, P = 0.02), but were mostly observed with LMA and less with ETT. Post-procedure pain was not different between groups, but flatulence was reported more with air insufflation ( P = 0.004). Conclusion: Transient elevations in EtCO2 occur more often with CO2 than with air insufflation during pediatric EGD despite protecting the airway with an LMA or, to a lesser degree, with ETT. These elevations were not associated with changes in MV. Although no adverse clinical effects from CO2 absorption were observed, these findings suggest that caution should be exercised when considering the use of CO2 insufflation, especially since the observed benefits of using this gas were minimal.